A response to COVID-19 and beyond: Expanding African capacity in vaccine production - Carlos María Correa (South Centre, 2023)
The unequal global distribution of vaccines against the deadly COVID-19 virus has cast a spotlight on the lack of access to vaccines on the African continent, and the vulnerability that such a lack places on both the economies of African nations and the health of their people. Various initiatives have been launched to overcome the dependence of African nations on vaccines produced elsewhere. If implemented in timely and effective ways, those initiatives will contribute to the diversification of African economies and strengthen the capacity of nations on the continent to address their public health needs during pandemics and at other times. While establishing a viable vaccine industry on the continent presents serious challenges, the African Continental Free Trade Area (AfCFTA) can provide the framework for leveraging economies of scale to stimulate the production of needed vaccines across the region.
Keywords: 300; Access to Medicines; Access to Vaccines; Africa; African Continental Free Trade Area (AfCFTA); African Union (AU); COVID-19; Global Health; Health; Intellectual Property; Pandemic; Public Health; Vaccine Equity; Vaccine Industry; Vaccine Inequity; Vaccine Nationalism; Vaccine Production; Vaccines